(untitled) (International Journal of Occupational Safety and Health, 2025)
Introduction: Construction industry is one of the most dangerous industries involving 5.5 millions work-related accidents and nearly 60,000 fatalities every year across the world. Near-Miss Reporting Systems (NMRS) is one of the proactive safety management options to identify hazards prior to any major accidents contributing to injury prevention. Although they are increasingly being adopted, the performance of NMRS in construction has never been exhaustively studied. This research evaluated the perceived effectiveness of the NMRS among construction employees and tested its relationship with other safety management practices and outcomes. Methods: A quantitative, cross-sectional, and correlational research design was used, gathering data from 475 construction workers in 18 Indian units and five-year accident and near-miss reporting trends. Descriptive analysis, Pearson correlation, and linear regression were applied to evaluate worker perceptions of NMRS effectiveness, safety interventions, and safety performance, as well as the relationship between accident and near-miss reporting trends. Results: The analysis demonstrated NMRS’s effectiveness in boosting safety awareness, preventing accidents [84.5% affirmation], and increasing job satisfaction [84.6% affirmation]. This effectiveness was strongly linked to robust safety management practices, including an open safety culture [r=0.56], regular safety audits [r=0.22], and employee engagement [r=0.16]. Critically, higher near-miss reporting frequencies correlated negatively with accident rates , signifying a proactive role of NMRS in reduction in incidents. Conclusion: NMRS effectiveness is closely tied to safety culture and management practices. Integrating NMRS into broader safety frameworks enhances construction site safety outcomes.